2014
DOI: 10.1128/mcb.00842-13
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between CD3 and CD28 Is Spatially Modulated by Protein Lateral Mobility

Abstract: dFunctional convergence of CD28 costimulation and TCR signaling is critical to T-cell activation and adaptive immunity. These receptors form complex microscale patterns within the immune synapse, although the impact of this spatial organization on cell signaling remains unclear. We investigate this cross talk using micropatterned surfaces that present ligands to these membrane proteins in order to control the organization of signaling molecules within the cell-substrate interface. While primary human CD4 ؉ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…Studies have shown that the cortical actin meshwork and the plasma membrane may interact directly (14) or indirectly via transmembrane and scaffolding proteins (4,15,16). We therefore hypothesized that the flow of the cortical actin mesh might be coupled to the membrane, causing retrograde membrane flow.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have shown that the cortical actin meshwork and the plasma membrane may interact directly (14) or indirectly via transmembrane and scaffolding proteins (4,15,16). We therefore hypothesized that the flow of the cortical actin mesh might be coupled to the membrane, causing retrograde membrane flow.…”
Section: Resultsmentioning
confidence: 98%
“…The cortical actin meshwork and the plasma membrane may interact directly (14) or indirectly via transmembrane and scaffolding proteins (4,15,16) including TCR (17), which has been observed to cause modulation of protein lateral mobility including trapping, tethering, and corralling (18). These sites of interaction frequently occur at areas of high membrane lipid order (12,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Except for the experiment of Fig. 3D, IFN-γ secretion was measured using a surface capture assay (Miltenyi) as previously described (17,18,27). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, mechanically trapping TCR nanoclusters at the peripheral regions of a forming synapse significantly prolonged and strengthened signaling from TCR nanoclusters [106]. However, separation of anti-CD3 and anti-CD28 contact sites by several microns in human T cells curtailed co-stimulatory activity [107]. Thus, while existing aAPC fabrication techniques generally rely on randomly distributed ligands, these findings suggest it may be possible to fine-tune T cell activation from aAPC by patterning activating ligands in ways that mimic T cell-APC interaction.…”
Section: Microscale T Cell-aapc Interactionsmentioning
confidence: 99%